2021
DOI: 10.2174/1871523019666200303104932
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Serum Procalcitonin Level as an Early Marker of Ascitic Fluid Infection in Post Hepatitic Cirrhotic Patients

Abstract: Background & Aims: The early diagnosis of spontaneous bacterial peritonitis (SBP) has been considered important in overall patient’s survival. Ascitic fluid culture examination performance, in the emergency setting, is time consuming and not always available, so there is a need for easy to apply, rapid and reliable markers to predict diagnosis in patients with ascites. This present prospective study aimed to determine the early diagnostic value of serum procalcitonin (PCT) levels in decompensated cirrhotic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…In our study, ascitic fluid procalcitonin was significantly elevated in patients with SBP than non-SBP, with a positive correlation with PMNL, which is the gold standard for the diagnosis of SBP. These results agree with the result from previous studies that reported high ascitic fluid procalcitonin in SBP patients [24,28]. Also, Yang et al [29] analyzed 339 patients with SBP from seven previous publications reporting serum procalcitonin levels is a relatively sensitive and specific test for the diagnosis of SBP.…”
Section: Discussionsupporting
confidence: 91%
“…In our study, ascitic fluid procalcitonin was significantly elevated in patients with SBP than non-SBP, with a positive correlation with PMNL, which is the gold standard for the diagnosis of SBP. These results agree with the result from previous studies that reported high ascitic fluid procalcitonin in SBP patients [24,28]. Also, Yang et al [29] analyzed 339 patients with SBP from seven previous publications reporting serum procalcitonin levels is a relatively sensitive and specific test for the diagnosis of SBP.…”
Section: Discussionsupporting
confidence: 91%
“…Yang et al, evaluated the diagnostic role of serum procalcitonin concentrations in patients with spontaneous bacterial peritonitis, where their results showed sensitivity 0.82 (95% C.I 0.79-0.87), specificity 0.86 (95% C.I 0.82-0.89), positive likelihood ratio 4.94 (95% C.I 2.28-10.70), negative likelihood ratio 0.22 (95% C.I 0.10-0.52), and diagnostic odds ratio 22.55 (95% C.I 7.01-108.30). The area under the curve was 0.92 [19,36]. Wu et al, found that serum procalcitonin levels in advanced liver cirrhotic patients with spontaneous bacterial peritonitis were significantly higher than those with (culturenegative neurolytic ascites).…”
Section: Discussionmentioning
confidence: 99%
“…As serum PCT levels increase earlier and normalize faster than CRP, it has benefit of earlier diagnosis of disease, as well as better follow up of the progression of the disease. Rapid identification of infection has a major effect on course, management, and outcome of critically ill intensive care unit (ICU) cases (8) .…”
Section: Introductionmentioning
confidence: 99%